The role of outcrops in the diversity of Patagonian vegetation: Relicts of glacial palaeofloras? - Speziale, Karina Lilian (2012)
Outcrops around the world enhance biodiversity as they provide heterogeneous environments and varied habitats for species with different requirements than those living in the surroundings, and in this way they increase alpha and beta diversity. We studied the floristic composition of the vegetation of rock outcrops in northwestern Patagonia, Argentina, and compared them to the surrounding matrix of shrubland and steppe. For this we sampled 50 outcrops and 50 matrix plots close to them, identified all the species present, and analyzed their floristic composition with Detrended Correspondence Analysis (DCA). We also analyzed the floras of the north and south faces of the outcrops. The resulting ordinations were related to geographic gradients of the region. The proportions of alien to native species, different life forms, and phylogenetic groups of the outcrop floras were compared to the matrix with G-tests. Our results showed similar dominant families, life form proportions and percentage of alien species in the outcrops and the surrounding matrix. However, species composition of the outcrops was markedly different. North Patagonian outcrops present several taxa not found in the matrix, especially in their southern, less insolated walls. The previously recorded distribution of most of these exclusive species is found in colder areas further south. Thus, we hypothesize that outcrops could be acting as relicts of cold-adapted glacial paleofloras that were probably more extended during glacial times and retreated south after the last glacial maximum. © 2011 Elsevier GmbH.